Photocatalytic degradation of ofloxacin antibiotic using g-C3N4/ZnO for wastewater treatment / Nor Fadilah Chayed ... [et al.] - Chayed, Nor Fadilah; Ibrahim, Mohd Lokman; Mashuri, Salma Izati Sinar; Mohd Kaus, Noor Haida; Mohd Sunhaji, Nur Nabihah (2024)
In recent decades, the healthcare sector has made significant advances in increasing global reliance on antibiotics. It has also raised concerns about the possibility of antibiotics causing environmental and biotoxicity problems. Ofloxacin (OFL) is a fluoroquinolone antibiotic used to treat gastrointestinal, urinary, respiratory, and skin infections. It has been found in aquatic environments, especially in pharmaceutical waste. Due to its high phytotoxicity, it poses an ecological risk to aquatic ecosystems and can promote the development of antibiotic-resistant bacteria. To completely remove the ofloxacin from the environment, effective methods are needed. Recently, photocatalysis has attracted much attention for its potential to effectively, economically, and environmentally friendly remove organic pollutants from wastewater. ZnO is known as a potential photocatalyst for the degradation of wastewater in the UV region. However, ZnO has limited light absorption within the UV region and exhibits fast recombination of electron-hole pairs, which reduces its efficiency. To overcome this issue, a g-C3N4/ZnO photocatalyst for organic pollutant degradation in wastewater was developed to extend the light absorption towards the visible region. This research aims to investigate the photocatalytic performance of g-C3N4/ZnO nanocomposites in the degradation of ofloxacin. The composite catalyst of g-C3N4/ZnO was prepared by mixing g-C3N4 and ZnO. The prepared catalysts were characterized for material properties investigation. As a result of the composite photocatalyst combining ZnO and g-C3N4, the degradation of ofloxacin is 11.5 times higher than pristine ZnO and double times higher than pristine g-C3N4.